2002
DOI: 10.1021/ja027149q
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal 1H Relaxation Optimization in TROSY NMR Spectroscopy

Abstract: A general method to enhance the sensitivity of the multidimensional NMR experiments performed at high-polarizing magnetic field via the significant reduction of the longitudinal proton relaxation times is described. The method is based on the use of two vast pools of "thermal bath" 1H spins residing on hydrogens covalently attached to carbon and oxygen atoms in 13C,15N labeled and fully protonated or fractionally deuterated proteins to uniformly enhance longitudinal relaxation of the 1HN spins and concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 30 publications
2
139
1
Order By: Relevance
“…This general signal loss can be minimized by maintaining a high steady-state water polarization throughout the experiment, which is usually achieved using selective ''flip-back'' pulses on the water resonance . Similar effects have been observed between the aliphatic proton resonances and the remainder of the spectrum in fully protonated large molecular systems (Akasaka et al, 1978), and it has been demonstrated that pulse sequences avoiding saturation of the covalently bound aliphatic protons yield more signal (Pervushin et al, 2002).…”
Section: Introductionsupporting
confidence: 63%
“…This general signal loss can be minimized by maintaining a high steady-state water polarization throughout the experiment, which is usually achieved using selective ''flip-back'' pulses on the water resonance . Similar effects have been observed between the aliphatic proton resonances and the remainder of the spectrum in fully protonated large molecular systems (Akasaka et al, 1978), and it has been demonstrated that pulse sequences avoiding saturation of the covalently bound aliphatic protons yield more signal (Pervushin et al, 2002).…”
Section: Introductionsupporting
confidence: 63%
“…First, the number of scans required to sample the multidimensional time space may be reduced by using spectral aliasing, nonlinear data sampling techniques, spatial frequency encoding, or Hadamard-type frequency-space spectroscopy (7,8). Second, accelerating the recovery of spin polarization between scans by means of optimized pulse sequences (9)(10)(11) or the addition of relaxation agents to the solution (12, 13) allows higher repetition rates of the pulse sequence. Here, we propose a fluid turbulence-adapted (FTA) version of 1 H-15 N 2D SOFAST-heteronuclear multiple quantum coherence (HMQC) (10,14) to follow a kinetic process for individual amide sites in a protein [see supporting information (SI) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As previously exploited in LTROSY (Pervushin et al, 2002) and SOFAST-HMQC (Schanda and Brutscher, 2005), the substantial H u polarisation recovered by the presented efb schemes can be used straightaway to indirectly replenish depleted H N polarisation during the subsequent interscan delay s (defined as the total delay between last and first proton pulse in consecutive scans). This constructive effect of dipolar H u !…”
Section: Accelerated H N Relaxation and Sensitivity Enhancementmentioning
confidence: 93%
“…The spin temperature of the ambient proton lattice thus importantly affects re-equilibration of the signal-generating proton subset, where T 1 relaxation progresses substantially faster under selective (with all except the selected proton spins near thermal equilibrium) than under unselective conditions (with uniformly depleted initial magnetisation for all protons). Experimentally cooling the spin temperature of the proton lattice can thus afford sizeable sensitivity gains through crossrelaxation accelerated polarisation recovery, as recently demonstrated for TROSY-type experiments (Pervushin et al, 2002) and 2D HMQC (Schanda and Brutscher, 2005).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation